Incidence and recurrence rate of postpartum hemorrhage and manual removal of the placenta: A longitudinal linked national cohort study in The Netherlands. (July 2019) - Ruiter, Laura; Kazemier, Brenda M.; Mol, Ben W.J.; Pajkrt, Eva
Abstract: Objective: We studied the incidence of postpartum hemorrhage and manual removal of the placenta and their recurrence rate in a subsequent pregnancy. We hypothesized that the risk of recurrence was dependent on the gestational age at first birth and whether or not a manual removal of the placenta was necessary. Knowledge on this subject can potentially improve counselling, prevention and management in obstetric care for women at risk for PPH or identify women at low risk for recurrence. Study design: This was a retrospective national cohort study consisting of women with two consecutive singleton deliveries between 1999 and 2009 in the Netherlands. A longitudinal linked national cohort with information on subsequent singleton deliveries in the Netherlands was used. Main outcome measures were: postpartum hemorrhage (defined as ≥1000 mL after vaginal delivery or Caesarean section) and manual removal of the placenta. We calculated incidence and recurrence rates of postpartum hemorrhage and manual removal of the placenta for all women and stratified by gestational age. Results: After application of in- and exclusion criteria 359 737 women were studied. A total of 5.4% women experienced postpartum hemorrhage in the first pregnancy and 2.7% of women had a manual removal of the placenta. The risk of postpartum hemorrhage in a subsequent pregnancy was significantly higher in women with a history of postpartum hemorrhage compared to women without a previous postpartum hemorrhage (18% vs 3.9%, adjusted odds ratio 4.5; 95% confidence interval 4.3–4.7). The risk of manual removal of the placenta in the second pregnancy was only 1.4% in women without a previous manual removal compared to 17% of women with a previous manual removal of the placenta. Women with a manual removal of the placenta in the first pregnancy between 32 and 37 weeks were most at risk for recurrence (adjusted odds ratio 8.9; 95% confidence interval 7.2–11). Conclusion: Women with a previous delivery complicated by postpartum hemorrhage or manual removal of the placenta are at increased risk for recurrence. The magnitude of this risk is highest in women with deliveries beyond 32 weeks in the first pregnancy.